Understanding the role of electrostatic interactions on the association of 5-fluorouracil to chitosan-TPP nanoparticles - dos Santos, Aline Martins [UNESP] (2022)
Judicious design strategies should be considered powerful tools to better control the properties of chitosan (CS) and tripolyphosphate (TPP) particles. This study focused on understanding the role of the charge properties of 5-fluorouracil (5-FU) on the formation and properties of CS-TPP nanoparticles. The effect of synthesis variables of CS-TPP nanoparticles (CS to TPP ratio and order of addition) under pH 4.5 and 5.5 was evaluated, where CS and TPP were charged, and 5-FU had two different charges (positive and negative), maximizing the interactions between them for the formation of nanoparticles. The order of addition and drug location resulted in changes in the interaction forces, influencing the particle size and size distribution. 5-FU addition into CS resulted in stronger interactions, favoring the formation of smaller particles. The pH of reactional medium and CS to TPP ratio affected the properties of particles, in terms of size and potential zeta, which led to greater 5-FU entrapment. These results demonstrated that the particle properties still depends of the synthesis factors, but the physicochemical properties of drug also influence the reactions/interactions involved in the formation of CS-TPP nanoparticles.